Implementing information requirements for GM commodities under the cartagena protocol article 18.2(A): at the national level: the case of Kenya - Gruère, Guillaume P.; Kimani, Virginia (International Food Policy Research Institute, 2010)
This note summarizes a study on the implications of implementing strict information requirements for genetically modified (GM) commodities under Article 18.2(a) of the Cartagena Protocol on Biosafety in Kenya. The results show that enforcement of strict “*does contain*” requirements, compared with the default “*may contain*” option, would create additional costs and challenges in the difficult implementation of import regulations.